LAS JURAS REALES A CARLOS IV EN LA CIUDAD DE MÉXICO Y EL PROYECTO DE IGNACIO DE CASTERA. - LIRA, SALVADOR; TERÁN ELIZONDO, MARÍA ISABEL (Dieciocho: Hispanic Enlightenment)
The article describes the project presented by Ignacio de Castera for the regal oath festivities to Carlos IV in Mexico City. The project included the manufacturing of platforms with portraits and emblems of the new monarch, as well as the construction of triumphal arches, statues, and an allegorical carriage. Castera proposed unifying different ceremonies and celebrating the festivities during the month of November to save expenses. His project integrated ritual, artistic, and economic aspects, and sought to perpetuate the memory of the sovereign.